Struktur Dayeuh Pakwan berdasarkan Pendekatan Morfologi - Andi Maryam Kadir; Weishaguna (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Dayeuh Pakwan Pajajaran is the capital of the Sunda kingdom which was born from the Hindu-Buddhist kingdom, the Tarumanegara Kingdom in the 4th century to the 7th century. As part of the Sunda Kingdom, various artifacts have been found but the spatial structure has not been well described. This study examines the structural form of Dayeuh Pakwan based on the findings of artifacts and four researchsources, namely (1) the results of previous studies, (2) the 15th century VOC map and VOC expedition reports, (3) the map of historian Nina Lubis, and (4) Results of observations and interviews. The analytical method used is the superimpose method with the analysis of (1) the land use of the palace, (2) the road network of the palace, and (3) the layout of the palace building. The results of this study are in the form of a map of the Pakwan Pajajaran dayeuh structure in the city of Bogor. Based on the results of the analysis, it can be concluded that: (1) Pakwan dayeuh land use is divided into 3 levels of sacredness based on the Tri Tangtu cosmology, (2) The structure of the palace road network is a well-organized and well-integrated main road lane, and (3) The results of the analysis of building layout with the Dayeuh Kawali concept divide the Dayeuh Pakwan area into 4 hierarchies. Abstrak. Dayeuh Pakwan Pajajaran merupakan ibukota dari kerajaan Sunda yang lahir dari kerajaan Hindu-Buddha yaitu Kerajaan Tarumanegara pada abad ke-4 sampai abad ke-7. Sebagai bagian dari Kerajaan Sunda, berbagai artefak telah ditemukan namun struktur ruangnya belum tergambarkan dengan baik. Penelitian ini mengangkat bentuk struktur Dayeuh Pakwan berdasarkan temuan artefak dan empat sumber penelitian yaitu (1) Hasil studi terdahulu, (2) Peta VOC abad ke-15 dan laporan ekspedisi VOC, (3) Peta ahli sejarah Nina Lubis, serta (4) Hasil observasi dan wawancara. Metode analisis yang digunakan adalah metode superimpose dengan analisis (1) Tata guna lahan keraton, (2) Jaringan jalan keraton, dan (3) Tata bangunan keraton. Hasil studi ini berupa peta struktur Dayeuh Pakwan Pajajaran di Kota Bogor. Berdasarkan hasil analisis maka dapat disimpulkan bahwa: (1) Penggunaan lahan Dayeuh Pakwan terbagi atas 3 tingkatan kesakralan berdasarkan kosmologi Tri Tangtu, (2) Struktur jaringan jalan keraton merupakan satu jalur jalan utama yang teratur dan terintegrasi dengan baik, dan (3) Hasil analisis tata bangunan dengan konsep Dayeuh Kawali membagi wilayah Dayeuh Pakwan menjadi 4 hirarki.